2010
DOI: 10.1007/s11144-010-0259-y
|View full text |Cite
|
Sign up to set email alerts
|

On the deactivation of alkali solid catalysts for the synthesis of glycerol carbonate from glycerol and dimethyl carbonate

Abstract: The deactivation of alkali solid catalysts for the synthesis of glycerol carbonate from glycerol and dimethyl carbonate was investigated. Calcium oxide, calcium hydroxide and calcium methoxide were chosen as the representatives of the alkali solid catalysts. When the catalysts were recycled, the yield of glycerol carbonate decreased dramatically. The alkali solid catalyst was converted to the basic calcium carbonate Ca x (OH) y (CO 3 ) z , which was the cause of the decrease of glycerol carbonate yield. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…2, the conversion after 1 h of operation and the TOF value were negligible and the TOF value were negligible at 55°C. Quantitative yields of GC were obtained using benzene [36] and tetrahydrofurane [37] as reaction media as opposed to the solventless operation approached in this study, in which a conversion of barely 3% was obtained at 60°C.…”
Section: Selection Of Temperaturementioning
confidence: 84%
“…2, the conversion after 1 h of operation and the TOF value were negligible and the TOF value were negligible at 55°C. Quantitative yields of GC were obtained using benzene [36] and tetrahydrofurane [37] as reaction media as opposed to the solventless operation approached in this study, in which a conversion of barely 3% was obtained at 60°C.…”
Section: Selection Of Temperaturementioning
confidence: 84%
“…The utilization of calcium methoxide had already been investigated for the transesterification of DMC and glycerol and it was observed that this catalyst suffered from deactivation. Such deactivation process takes place through a complex reaction network in which calcium methoxide is eventually transformed into basic calcium carbonate, represented by the formula Ca x (OH) y (CO 3 whose basic strength is much lower than the original Ca(CH 3 O) 2 or calcium diglyceroxide, which is the species initiating the reaction mechanism for reaction {a} [42]. Subsequently, Models {a}3 and {a}4 are herein presented to take into account a first order catalyst deactivation in which an analogous basic potassium carbonate species would be formed.…”
Section: Kinetics Of Reaction {A}: Transesterification Of Glycerol Wimentioning
confidence: 99%
“…Additionally, potassium methoxide has been utilized jointly with the ionic liquid [BMIM][Br] to achieve the electrochemical valorisation of CO 2 giving DMC as a product [41]. Finally, the solid catalyst calcium methoxide has also been used for the transesterification of glycerol with DMC [42].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the case of calcium methoxide, when used for the production of glycerol carbonate, deactivation proceeds by a successive hydration to form the hydroxide followed by carbonation to render a mixed hydroxide-carbonate, a much less effective catalyst for transcarbonation reactions [50] . If potassium is considered, mixed salts are not expected as they are fully soluble (which is not the case of the alkaline earth element), but potassium hydroxide is scarcely soluble in organic solvents, even in glycerol at low to moderate temperatures.…”
Section: Proposal and Discrimination Of The Kinetic Model Of The Reacmentioning
confidence: 99%